Association of systemic lupus erythematosus with peripheral arterial disease: a meta-analysis of literature studies. (13th August 2020) - Forte, Francesco; Buonaiuto, Alessio; Calcaterra, Ilenia; Iannuzzo, Gabriella; Ambrosino, Pasquale; Di Minno, Matteo Nicola Dario
Abstract: Objective: SLE patients have an increased cardiovascular morbidity and mortality. Contrasting data are available about the association between peripheral arterial disease (PAD) and SLE. We aimed to perform a meta-analysis of studies evaluating the association between SLE and PAD. Methods: Studies were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases according to preferred reporting items for systematic reviews and meta-analyses guidelines. Results: Eight studies reporting on 263 258 SLE patients and 768 487 controls showed that the prevalence of PAD was 15.8% (95% CI: 10.5%, 23.2%) in SLE patients and 3.9% (95% CI: 1.8%, 7.9%) in controls with a corresponding odds ratio of 4.1 (95% CI: 1.5, 11.6; P <0.001). In addition, five studies reporting on ankle-brachial index showed significantly lower values in 280 SLE patients as compared with 201 controls (mean difference: − 0.018; 95% CI: − 0.034, − 0.001; P =0.033). Meta-regression models showed that age, hypertension and diabetes were inversely associated with the difference in the prevalence of PAD between SLE patients and non-SLE controls, whereas no effect for all the other clinical and demographic variables on the evaluated outcome was found. Conclusion: SLE patients exhibit an increased prevalence of PAD and lower ankle-brachial index values as compared with non-SLE controls. This should be considered when planning prevention, interventional and rehabilitation strategies for these chronic patients with functional disability and poor long-term outcomes.